Penganggaran Untuk Pengendalian Organisasi Di BUMDes Rukun Makmur - Sukma Mardaning Poncowati; Noni Christia Firdianti; Aditya Pradina Hermawan; Niken Wahyuningtyas; Faneshia Tangke Rerung; Hafid Pramaisvara; Agnes Deta Ardina (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
Organizational control is needed by both business and non-business organizations, business organizations have the main goal of getting profit and for non-businesses it has a goal for public services. Village-Owned Enterprise (BUMDes) "Rukun Makmur" is located in Jetak Village, Semarang Regency and has three types of business units, including the Stationery and Photocopy Sales Business Unit, the Material Sales and Heavy Equipment Rental Business Unit (Molen), and the Non-Cash Food Assistance Business Unit (BPNT). The purpose of community service activities is to identify weaknesses in organizational control that exist in the Village-Owned Enterprise (BUMDes) organization and provide recommendation for appropriate strategies for the development of BUMDes.It is hoped that BUMDes managers will get a better understanding of the organizational control conditions and strategies that should be carried out.